2020 Young Investigator Award Winner: Age- and Sex-related Normative Value of Whole-body Sagittal Alignment Based on 584 Asymptomatic Chinese Adult Population From Age 20 to 89 - Hu, Zongshan; Man, Gene Chi Wai; Yeung, Kwong Hang; Cheung, Wing Hoi; Chu, Winnie Chiu Wing; Law, Sheung Wai; Lam, Tsz Ping; Zhu, Zezhang; Qiu, Yong; Cheng, Jack Chun Yiu (Spine (Philadelphia, Pa. 1976), 2020)
A cross-sectional radiographic study. The aim of this study was to establish the age- and sex-related normative values of whole-body sagittal alignment in asymptomatic Chinese adult population, and to investigate the changes and possible associated compensation mechanisms across age groups. Previous studies have reported normative data for sagittal spinal alignment in asymptomatic adults. However, there was a lack of comprehensive investigation on age- and sex-related normative values of whole-body sagittal alignment. A total of 584 asymptomatic Chinese adults aged 20 to 89 years were recruited. Subjects were grouped according to age and sex. Whole-body standing radiographs were acquired for evaluating sagittal alignment from spine to lower limb. Comparisons of sagittal parameters between sex in different age groups were performed by independent t test. Pearson correlation analysis was used to determine relationships between each parameter. Mean values of each sagittal parameter were presented based on age and sex. Thoracic kyphosis showed steady increasing trend while lumbar lordosis gradual decrease in both sexes. Pelvic tilt (PT) in males is greater than in females across all age groups with age-related gradual increase. There were significant differences between males and females from 20 to 60 years in terms of KneeFlex angle (KA) and AnkleFlex angle, but the differences were not significant after 60s. T1 pelvic angle (TPA) was significantly correlated with spinal, pelvic and lower-limb alignment. The older group (≥50 years) had a stronger correlation of TPA with PT and KA, whereas the younger (<50 years) had stronger correlation with TK. This study presented a comprehensive study of whole-body sagittal alignment based on a large asymptomatic population, which could serve as an age- and sex-specific reference value for spine surgeons when planning for correction surgery. Age can influence the recruitment of compensation mechanism that involves more pelvic and lower limb mechanisms for elderly people. 3.